Grafiti u Delilovom Podzemlju (Philologia, 2021)
The paper deals with DeLillo’s representations and interpretations of various graffiti types in his Underworld. There are several episodes, discussions and accounts of graffiti practices in the novel, so that DeLillo’s attitudes toward these practices, their aesthetics and politics, and his view of their relationships with other cultural movements, creative industries and artistic forms and genres are the topic of this research. The influences of these graffiti forms and styles on the work of Clara Sax, as presented in the novel, and her re-interpretation and re-appropriation of graffiti artists’ stylistic devices and motivations are accentuated.
Keywords: grafitti; nose art; politics of art; subculture